Bug Hunter : Nature Activities - Burnie, David (London Dorling Kindersley Ltd, 2005)
Describes what is involved in studying bugs and presents projects and activities for collecting and observing them.
Include Color Illustrations and Glossary
Keywords: Insects -- Juvenile literature